Numerical Investigation on Stratum and Surface Deformation in Underground Phosphorite Mining Under Different Mining Methods - Li, Xiaoshuang; Wang, Yunmin; Hu, Yunjin; Zhou, Changbing; Zhang, He (Frontiers in Earth Science, 2022)
With the ending of deep-concave open-pit phosphorite extractions and the gradual exhausting of shallow mineral resources, stoping of phosphorite seams has entered or will enter into underground mining. Particularly for excavating slightly inclined thin and medium-thick phosphorite orebodies, roof and surface control under different mining methods is crucial for safe and efficient exploitations. In this paper, the study area is located in Kunyang Phosphorite Mine characterized by slightly inclined thin and medium-thick deposits. Based on the occurrence conditions, orebody thickness, dip angle and more, the mining methods of underground phosphorite are selected, including room and pillar mining, cement backfill mining and caving mining. Numerical analysis on roof deformation and surface subsidence under the three methods is performed. The results show that the amount of roof and surface subsidence decreases successively by the caving method, room and pillar method and cement backfill method. The maximum roof and surface subsidence by the caving method is 45.7 cm and 13.3 cm, respectively. Regarding shallow orebodies, the open-pit slope is obviously disturbed by the caving method and room and pillar mining method. Hence, slope displacement monitoring should be emphasized. Compared with the other two methods, the backfill mining method can use mined wastes as backfill materials, but also has less influence on the roof and the surface during stoping and is better at controlling the slope stability.